Penerapan E-Banking Dan Green Banking Dalam Meningkatkan Kualitas Layanan Perbankan - Abdullah Umar; Muhammad Iqbal Fasa; Suharto Suharto; Adib Fachri (Tirtayasa Ekonomika, 2023)
The purpose of this research is to see the implementation of E-Banking and Green Banking in improving banking services and services at PT. Bank Negara Indonesia. An example of this research is the number of E-Banking users and the number of customers of PT. Bank Negara Indonesia from 2016 to 2021 and the impact of energy use from 2019 to 2021. This study uses qualitative data analysis as a research method that describes descriptively the application of E-Banking and Green Banking in Improving the Quality of Banking Services at PT. Bank Negara Indonesia.. These results show the implementation of E-Banking at PT. Bank Rakyat Indonesia in accordance with the standards set by Bank Indonesia, the implementation of E-Banking can improve the quality of banking services and services as well as increase customer loyalty PT. Bank Negara Indonesia.